Analisis Forensik Untuk Mendeteksi Pesan yang Disembunyikan pada Short Message Service Menggunakan Aplikasi Berlisensi Open Source - Ike Yunia Pasa; Dedy Hariyadi (Universitas PGRI Kanjuruhan Malang, 2020)
Anti Forensic Techniques aim to complicate the process of investigating a crime. Hiding an SMS message with the aim or support of a crime can be categorized as an Anti Forensic technique. On smartphones with the MIUI operating system, it is equipped with features to block an SMS message and even hide an SMS message. The existence of a feature to hide SMS messages will complicate the investigation process if this feature uses to support crime. This research proposes a forensic analysis method to detect hidden SMS messages using open-source software. Differences in the process of retrieving digital evidence will affect the results of forensic analysis. So in this research to compare the results of the analysis of two digital forensic software to detect hidden messages.